Land Use and Land Cover Change: A Comprehensive Review of Environmental Implications - Shreya Singh (International Journal of Land, 2024)
Changes in land use and cover have a substantial impact on environmental dynamics and sustainability. These changes arise from various human activities, including urbanization, agriculture, and forestry, and have profound implications for biodiversity, ecosystem services, and land health. As urban areas expand, often at the expense of agricultural and forested landscapes, the transformation of land use alters ecological processes, leading to habitat loss and fragmentation. This article examines the implications of land use change, highlighting its role in shaping ecosystem dynamics and the environment. Urbanization is one of the most pronounced drivers of land use change in contemporary society. Cities are rapidly expanding due to population increase and economic development, resulting in the conversion of natural habitats into constructed environments. This transformation not only contributes to biodiversity loss but also disrupts essential ecosystem functions, such as carbon storage and water purification. The article emphasizes the need to understand the interrelationship between urban development and ecosystem health, advocating for urban planning practices that prioritize sustainable land use. In addition to urbanization, agricultural expansion has a significant impact on land use change. The demand for food production drives the conversion of forests and grasslands into agricultural fields, resulting in deforestation and the loss of valuable ecosystems. Agricultural intensification often leads to practices that exacerbate soil erosion and land degradation, further diminishing land health. This article discusses how these agricultural practices can create a feedback loop that exacerbates environmental challenges, ultimately threatening food security and ecosystem integrity. The consequences of land cover change, particularly habitat fragmentation and the degradation of ecosystem services, are explored in depth. Habitat fragmentation disrupts wildlife populations and reduces genetic diversity, making ecosystems more vulnerable to climate change and other anthropogenic pressures. The degradation of ecosystem services, such as pollination, soil fertility, and water regulation, poses significant risks to human well-being and environmental sustainability. By emphasizing the importance of conserving biodiversity and maintaining ecosystem services, the article advocates for integrated land use planning that considers ecological health. Soil erosion and soil degradation are major issues resulting from land use change, particularly in agricultural environments. Intensive farming operations deplete topsoil, limiting agricultural production and leading to sedimentation in streams. This article highlights the need for sustainable agricultural practices that enhance soil conservation and restore degraded lands, thereby promoting ecosystem resilience. Finally, effective land governance and tenure security are essential for addressing the multifaceted challenges associated with land use and land cover change. Strong governance frameworks can help to reduce land-related conflicts and encourage sustainable land management practices. The article underscores the importance of securing land tenure for marginalized communities, ensuring equitable access to land resources, and fostering collaboration among stakeholders. In conclusion, understanding land use and land cover change is vital for developing effective strategies to address environmental challenges and promote sustainability. By integrating ecological considerations into land use planning and governance, it is possible to enhance ecosystem health while meeting the demands of a growing population.
Keywords: Land use change; agricultural expansion; biodiversity conservation; deforestation; ecosystem services; land cover change; land governance; land tenure; soil erosion; urbanization